PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOSIAL RESPONSIBILITY DISCLOSURE PADA RETURN SAHAM - Pratiwi, Nining; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 9 No 2 (2014), 2014)
The main target of a corporation is to maximize shareholder wealth. How to maximize shareholder wealth is to increase the company's stock return. Good Corporate Governance and Corporate Social Responsibility is an activity that allows triggers an increase in stock returns. This study aimed to examine the effect of good corporate governance and corporate social responsibility disclosure on stock returns of listed companies in Indonesia Stock Exchange 2010-2012. This study used purposive sampling method to determine the choice of samples which are then acquired 10 companies, with multiple linear regression analysis as a method of hypothesis testing. The analysis finds that the F statistic test shows that the regression model used is considered viable and the company is able to predict stock returns. T-test results found that good corporate governance does not have a significant effect on stock returns, while Corporate Social Responsibility Disclosure significant effect on stock returns.
Keywords: good corporate governance, corporate social responsibility, return saham